Characteristics of Physicochemical Properties of Sago Starch (Metroxylon spp.) Varieties Rondo from Papua and Meranti from Riau - Kiptiyah, Sakina Yeti; Virdamayana, Khaerunnisa; Khairiah, Khairiah (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2024)
Indonesia has more than 90% of the world's sago area, 85% of which is in Papua Province and Western Indonesia, including Meranti Islands Regency and Riau Province. According to the Ministry of Agriculture of the Republic of Indonesia, the western region of Indonesia is the largest producer of sago production in Indonesia. The purpose of this study was to determine the physicochemical properties of sago starch of the rondo variety and the physicochemical properties of sago starch of the meranti variety. This research design used statistical analysis using a normality test then a uniformity test and continued with a repeated t test 6 times on sago flour from the Papua Rondo cultivar and the meranti cultivar from Riau. The parameters measured in this study were swelling and solubility, moisture content and carbohydrate content. The results of the study concluded that there were differences between the two types of arrowroot starch. The water content of sago starch (8.25%) of the rondo variety from Papua had a real influence on the water content of sago starch (13.5%) of the meranti variety of Riau, but did not have a real influence on its swelling capacity, solubility and carbohydrate content. An innovative product that is in accordance with the characteristics of sago flour from the rondo variety from Papua and the meranti variety from Riau is a biscuit.